New concepts in asthma: clinical phenotypes and pathophysiological mechanisms. Issue 2 (February 2017) - Koczulla, Andreas R.; Vogelmeier, Claus F.; Garn, Holger; Renz, Harald
Highlights: This review gives an overview of the recently discussed phenotypes and describes possible underlying endotypes in asthma. The interrelationship between clinical phenotypes and molecular endotypes will be addressed. New therapeutic concepts, based on the improved understanding of endotypes, are introduced. Abstract : Asthma is among the most common chronic inflammatory diseases worldwide. Recent evidence indicates that the pathogenesis shows a high degree of heterogeneity. Patient subsets have been identified that exhibit different cellular and molecular patterns of dysregulation. A prominent example is eosinophilic Th2-driven asthma. These unique and molecular patterns are termed endotypes. Characterization of endotypes has broad implications for therapeutic interventions. Although ∼80% of asthmatic patients respond well to standard anti-inflammatory therapies, the remaining subset particularly consisting of severe patients requires a more specialized endotype-specific approach. This interrelationship between clinical phenotypes, molecular endotypes and endotype-specific therapies is the focus of this review.